Dissemination of Kaffah Model of Learning through In House Training (IHT) - Syahrial Ayub; Joni Rokhmat; Agus Ramdani; Aliefman Hakim; AA Sukarso; Endang P Handayani (Postgraduate Program, University of Mataram, 2023)
This study describes the responses of prospective teacher students to learning the Bernoulli principle. The research design used descriptive research with a sample of 38 prospective teacher students from PGMI State Islamic University of Mataram. Data was obtained from response questionnaires with 3 indicators, namely happy, easy to understand and useful. As a result, the response of prospective teacher students to Kaffah learning is very good and has a positive impact on them. Kaffah learning integrates religion, science, application and meaningfulness from a single concept. This learning is expected to contribute to the development of the ability of prospective teacher students in planning, implementing and evaluating learning.